Multi-Product Pricing and Minimum Resale Price Maintenance - Markus Dertwinkel-Kalt; Christian Wey (ZBW - Leibniz Information Centre for Economics, 2021)
We provide a novel explanation for why manufacturers want to enforce a minimum resale price (min RPM) on retailers. A manufacturer sells her good via a multi-product retailer to final consumers by charging a linear wholesale price. The manufacturer then maximizes her profit through min RPM whenever the Edgeworth taxation paradox (ETP) occurs, that is, whenever the retailer could increase profits by decreasing all prices. Unlike many other justifications for RPM, our ETP-driven explanation for min RPM critically relies on interbrand competition, and it is-at least in the case of linear demand functions-always to the detriment of consumers.
Keywords: L12; L41; D42; K21; 330; Resale Price Maintenance; Vertical Restraints; Retailing